Alternative Specification and Estimation of Tax Revenue-Gross Domestic Product Relationship - Edeme, Richardson Kojo; Nkalu, Chigozie Nelson; Azu, Benedict; Nwachukwu, Sylvernus Chinedu (Asian Journal of Economic Modelling, 2016)
In fiscal economics, tax has been recognized as veritable instrument in generating revenue and stabilizing growth. However, to determine if a country has made efforts at increasing tax revenue over a period, tax performance in the dynamic sense which measures the sensitivity and response of the tax revenue in relation to GDP is imperative. Motivated by this, we adopted the buoyancy approach to examine Tax revenue-GDP relationship using Nigeria data. This is to ascertain if the government is keeping track on tax revenue mobilization as GDP is on a continuous increase. Besides, the estimation of tax buoyancy for Nigeria is very useful in understanding the overall tax revenue performance in the economy. The finding indicates that although the rate of growth in GDP has been fairly high, Tax-GDP ratio has not grown rapidly over the past years.